Competitiveness and Specialisation of the Austrian Export Sector - A Constant-Market-Shares Analysis - Edith Skriner (FIW - Research Centre International Economics, 2009)
This constant-market-shares (CMS) analysis shows the development of competitiveness, market and product structure of the Austrian merchandise exports from 1990 to 2006. The traditional CMS application was transformed to a dynamic model, such that the static indicators have been replaced by time series. This dynamic consideration of the CMS analysis helps to track all changes in the trade structure and competitiveness over time. The long-term trend of the indicators suggests that the Austrian foreign trade sector was able to maintain its market share in the global environment. While the Austrian foreign trade performance only slightly deviates from the pattern of the traditional industrialised countries, a strong structural change is observable in the external sector of the emerging markets. The disadvantages in competitiveness of the Austrian foreign sector have vanished, however, the market and product structure effects show negative trends after 2000, pointing to vulnerability in the Austrian export sector.
Keywords: F1; F14; C22; C43; 330; Welfare International economics; trade; countries and industry studies of trade; index numbers and aggregation; time series models